The Scenario of Dengue-like Illness in Paediatric Population of Southern Bangladesh - Rahman, M Luthfor; Rashid, AKM Mamunur; Debnath, Mithun; Islam, Tasnuva (TAJ: Journal of Teachers Association, 2021)
Dengue is one of the most important mosquito-borne viral diseases affecting humans. Dengue infections can result in a broad spectrum of disease severity ranging from an influenza-like illness (DF) to the life-threatening dengue hemorrhagic fever (DHF)/dengue shock syndrome (DSS). Although adults do experience shock, vascular leakage is generally more severe in young children, and in endemic areas, DSS is seen primarily in the pediatric population. The detailed clinical and laboratory profile is crucial for the diagnosis and the successful management of the patients. This study aims to observe the clinical features and laboratory results for the better understanding of patient management to reduce child death in case of dengue fever. A prospective cross-sectional study was conducted at the dengue ward of Khulna Medical College Hospital; 167 suspected dengue patients were enrolled in our research during the period from 7th August to 8th November 2019. Patients attending the emergency department and pediatric outpatient department with complaints of fever and features of dengue with positive NS1 antigen test and/or positive dengue specific antibody IgM or IgG or both were included in this study. Diagnosis of dengue was made on the basis of compatible clinical features and NS1 antigen positivity and/or detection of IgM and IgG antibodies. Patients were classified according to WHO 2012 protocol, and data was analyzed. One hundred sixty patients (95.8%) were diagnosed as having dengue illness, and the rest 7(4.2%) as fever other than dengue. Among the dengue illness, dengue fever (DF) 87(52.1%), DF with warning signs 51(30.5%), DHF 19(11.4%), and DSS 3(1.8%).The most common sign-symptoms of dengue was fever(100.0%),vomiting(52.1%),abdominal pain(38.3%), headache(23.4%),skin rash(13.25%), melena (7.8%), abdominal tenderness(28.7%),palpable liver (24.6%),and palpable spleen(3.0%). NS1 antigen was found positive in 88.6% cases, negative 3.0%, and NS1 antigen test not done 8.4% cases due to time constrain. Anti-dengue antibody IgM positive in 10(6.0%),IgG positive 7(4.2%),both IgM & IgG positive 7(4.2%),both IgM & IgG negative 57(34.1%) and antibody test not done in 86(51.5%) cases due to time constrain. Anti-dengue antibody not done in 86(51.5%) cases; among them most of the cases (98.8%) are found NS1 positive and 1.2% NS1 test negative(P<0.001) in our study which is statistically significant. Observation of clinical and laboratory parameters is helpful for dengue classification and management to reduce child death. TAJ 2021; 34: No-1: 86-96